A categorização e a delimitação de uma unidade de conservação como subsídio à sua criação: o caso do Morro Gaúcho, em Arroio do Meio e Capitão/RS - Thomas, Bruna Letícia (2013)
Morro Gaúcho, located between the cities of Arroio do Meio and Capitão (RS), is characterized by its remnants from the Mata Atlântica biome besides being a regional touristic spot. As a way to have environmental protection, in 2002 and 2010, there were discussions about the creation of a Conservation Unit (CU) on site. However, conflicts with the local population and lack of knowledge about the concepts, categories and boundaries caused the abandonment of the municipal government to continue negotiations. However, despite the withdrawal, creating a CU in Morro Gaucho is relevant for the effective protection and maintenance of the remaining forests. Thus, the need for the development of this research is indispensable. Providing information and the necessary limits, this study seeks to strengthen a new attempt to create the CU. Therefore, one of the main objectives was to identify which category is most appropriate to define a territorial limit for the future of the CU Morro Gaucho. The categorization and definition of CU are important since many CUs were framed in improper categories when created, regarding their environmental characteristics and management objectives. As a consequence of inadequate limits, ineffective and negative results emerged regarding the protection of the attributes present in the area. In order to get the results, a wide part of the study area was environmentally characterized aiming to find out about physical, biological and man-made attributes of the landscape through thematic mapping and field work; analyze the objectives, features and specifications of the categories of CUs present in the National System of Nature Conservation Units (SNUC) and State System of Conservation Units (SEUC) was another goal and assisted in the process of choosing the best category, taking into account the results of previous goals; and finally, the study aimed to define the perimeter of the proposed CU, being the vegetation the main element to be analyzed. From the results of the environmental characterization and analysis of the CU categories, two protected areas emerged, an Area of Ecological Interest and an Area of Environmental Protection, aiming that both areas of environmental protection act complementarily in Morro Gaucho. The results of this research are important for strengthening the process of creating the CU site since previously there was the lack of information and limitations; the future protected area hampered the negotiations about the creation of a CU.